Hybrid Digital Coding Metasurface for Independent Control of Propagating Surface and Spatial Waves. Issue 13 (2nd May 2019) - Wang, Meng; Ma, Hui Feng; Wu, Liang Wei; Sun, Shi; Tang, Wen Xuan; Cui, Tie Jun
Abstract: A metasurface is a kind of planar metamaterial made by placing subwavelength‐scale structures into a 2D pattern on a surface or interface. It has been attracting much attention in recent years. In this paper, a concept for a hybrid digital coding metasurface is proposed that can manipulate the radiation of surface waves (SWs) and spatially propagating waves (SPWs), independently and simultaneously, in the same frequency band. By independently controlling the coding sequences of digital elements "0" and "1" for surface impedance and metasurface reflection phase, the SW radiation and SPW reflection can be reconfigured and manipulated in both the elevation and azimuth directions, respectively, with weak mutual coupling. To the best of our knowledge, this is the first attempt to simultaneously manipulate SW and SPW radiation using only a single metasurface with a shared aperture. Full‐wave simulations and experimental measurements are presented to validate the proposed theory and new physical phenomena. Abstract : A hybrid coding metasurface that can independently manipulate surface waves (SWs) and spatially propagating waves (SPWs) is proposed. By independently controlling the coding sequences of digital elements "0" and "1" for surface impedance and reflection phase of the metasurface, the radiations of SWs and SPWs can be reconfigured and manipulated, respectively, which has potential applications in multiantenna multiplexing.